THE NATURE, MEANING AND PURPOSE OF PUNISHMENT AS PHILOSOPHO-LEGAL CATEGORIES - Denysova, Tetyana A. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Objective: the paper focuses on attempts to show, first of all, the potential capacity of the meaning of the “punishment” concept as enshrined by law, by way of construing certain philosophical categories such as nature, meaning, form, purpose and clarifying the functions thereof within the scope of the “punishment” concept definition; to establish characteristic features and peculiarities of punishment which actually predetermine the substance of such criminal law institution; and, thus, to shed a clearer light onto how and to what extent punishment may influence on the crime rate reduction. Results: the existing scientific approaches to definition of nature and meaning of the “punishment” concept have been analysed, and there has been also shown their interrelation with the notions of purpose and function of punishment. There has also been stated that the problem in question is impossible to explore without having construed the philosophical categories of nature, meaning, form, and purpose in attempt to define the notion of punishment. The focus has been placed on the necessity to directly address the philosophical categories in order to understand the nature and meaning of punishment, since any legal phenomenon comprises its own peculiar specific features and can be elucidated only either by means or with the help thereof. Discussion: there are reasonable grounds to claim that the nature of punishment is not identical to such notions as “meaning”, “form”, “purpose”, and “function”. It shall be defined largely by the essence of those aims that government attempts to achieve when applying this specific type of social relations regulator. Meaning specifies the nature of punishment. It has been noted that future research prospects on this issue are feasible if the focus is placed on elaboration of contemporary approaches and characteristics of such fundamental categories of legal science as nature, meaning, form, functions, and purpose of punishment.